2000
DOI: 10.1016/s1010-7940(00)00380-8
|View full text |Cite
|
Sign up to set email alerts
|

Coronary surgery in Europe: comparison of the national subsets of the European System for Cardiac Operative Risk Evaluation database

Abstract: There are important epidemiological differences in the national cohorts of CABG patients in the EuroSCORE database. Any international comparison of European surgical results must therefore take into account the risk profile of patients by using a compatible risk stratification system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 2 publications
0
38
1
5
Order By: Relevance
“…A total of 600 patients were excluded to rule out these early postoperative adverse events causing RBC transfusion, leaving 4,465 patients in the further analysis. For the primary analysis, assessing the association between RBC transfusion and outcomes in uncomplicated study patients, additional 3,520 patients were excluded from the 4,465 patients for (4) hemoglobin \10 g/dl, or missing data for hemoglobin at admission to the intensive care unit (n = 1,905); and/or (5) blood loss via chest tube C250 ml, or missing data for blood loss via chest tube in the first 4 postoperative hours (n = 1,982); and/or (6) severe blood loss or missing data for blood loss in the first 24 postoperative hours ([100 ml/h for any of the first 24 h, or a total of C1,000 ml for the first 24 h, n = 2,487); and/or (7) high risk for postoperative mortality by the European System for Cardiac Operative Risk Evaluation (EuroSCORE C8, n = 644) [18,19]. The effect of RBC transfusion on cardiac events as well as other multiorgan outcomes was evaluated in the 945 uncomplicated study patients who underwent CABG surgery (18.6% of the 5,065 McSPI EPI II study patients, Fig.…”
Section: Clinical Carementioning
confidence: 99%
“…A total of 600 patients were excluded to rule out these early postoperative adverse events causing RBC transfusion, leaving 4,465 patients in the further analysis. For the primary analysis, assessing the association between RBC transfusion and outcomes in uncomplicated study patients, additional 3,520 patients were excluded from the 4,465 patients for (4) hemoglobin \10 g/dl, or missing data for hemoglobin at admission to the intensive care unit (n = 1,905); and/or (5) blood loss via chest tube C250 ml, or missing data for blood loss via chest tube in the first 4 postoperative hours (n = 1,982); and/or (6) severe blood loss or missing data for blood loss in the first 24 postoperative hours ([100 ml/h for any of the first 24 h, or a total of C1,000 ml for the first 24 h, n = 2,487); and/or (7) high risk for postoperative mortality by the European System for Cardiac Operative Risk Evaluation (EuroSCORE C8, n = 644) [18,19]. The effect of RBC transfusion on cardiac events as well as other multiorgan outcomes was evaluated in the 945 uncomplicated study patients who underwent CABG surgery (18.6% of the 5,065 McSPI EPI II study patients, Fig.…”
Section: Clinical Carementioning
confidence: 99%
“…The average number of bypasses performed was 3.01 per patient. The mean Euroscore of the patients was 6.0, which is higher than the European average [23]. None of the patients included in the study deceased and no cases of myocardial infarct, stroke or kidney failure were reported.…”
Section: Resultsmentioning
confidence: 81%
“…However, when RA grafts are considered, the potential advantages on short-term prognosis are still questioned. Therefore, it does not surprise that SV grafting continue to be the back-bone of daily practice either in US and Europe [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies reported a higher patency of RA-CABG compared to SV-CABG, because of a better harvesting technique [3], the use of a pedicled conduit [4], a better "tailored" indication to severely stenosed (N80%) coronaries [5], and so on. However, SV continue to be extensively used, and represent the second employed conduit in both STS National Database and EuroSCORE Database [6,7]. Moreover, surgeons have recently acquired the possibility for an intraoperative functional assessment of the quality of their CABG, with the aid of the transit-time flow technology (TTF), whose intraoperative results furthermore predict graft patency at mid-term angiographic follow-up [8].…”
Section: Introductionmentioning
confidence: 99%